A link between human papilloma virus vaccination and primary ovarian insufficiency: current analysis. Issue 4 (August 2015) - Gruber, Noah; Shoenfeld, Yehuda
Abstract : Purpose of review: The cause of primary ovarian insufficiency (POI) is multifactorial. Known causes include external factors such as chemotherapy, radiotherapy, exposure to endocrine-disrupting chemicals, infections that lead to a permanent insult to the ovary, autoimmune conditions, and genetic causes. An association between the quadrivalent antihuman papilloma vaccine (HPV4) and POI was recently suggested. Recent findings: An increasing number of cases of POI post-HPV4 are being reported. Possible mechanisms for the suspected effect of HPV on female reproductive function are a toxic effect or an autoimmune response. The trigger could be the vaccine immunogen contents or the adjuvants, the latter are used to increase the immune reaction. The adjuvant in HPV4 contains aluminum. Animal models have shown aluminum exposure to inhibit expression of female reproductive hormones and to induce histologic changes in the ovaries. Specific genetic compositions may be more susceptible to developing an autoinflammatory syndrome after exposure to an environmental factor. Summary: The mechanisms responsible for POI are not yet fully understood. Although case reports cannot establish causation, awareness of a possible link between HPV4 and POI will help to identify and manage future cases that may arise.